Revealing the relationship between acceptance and understanding of evolution through NOS (Nature of Science)-based learning - Shefa Dwijayanti Ramadani; Ika Sukmawati (JURNAL BIOEDUKATIKA, 2022)
Evolution is considered the central and unifying theme of the discipline of Biology. Yet, some debates refusing the theory of evolution raise and lead to a problem in understanding the evolution process. This study aimed to examine the relationship between acceptance and understanding of the concept of evolution in pre-service biology teachers with solid religious and educational backgrounds. A correlational design was employed in this current study. The study subjects were students of the Biology Education Department of Universitas Islam Madura, which has implemented NOS (Nature of Science)-based learning. All subjects are Muslims, and 86.84% pursued their education in Islamic boarding schools. The data was measured using MATE (Measure of Acceptance of the Theory of Evolution) and ECK (Evolution Content Knowledge). The study’s findings indicate a significant relationship between acceptance and understanding of the concept of evolution. In addition, the acceptance of the concept of evolution contributed 63.6% towards the understanding. These findings suggest that acceptance of evolution is essential to understand it and that teaching evolution by implementing NOS-based learning is a necessary step to improve students’ acceptance and understanding of the concept of evolution.